An Ivory Rod with a Cuneiform Inscription, Most Probably Ugaritic, from a Final Palatial Workshop in the Lower Citadel of Tiryns - Cohen, Chaim; Maran, Joseph; Vetters, Melissa (Archäologischer Anzeiger, 2014)
The subject of this contribution is the fragment of an ivory rod with six cuneiform signs that was found in 2002. The rod came to light in a destruction layer dating to LH III B Final within a workshop for skilled crafting inside Building XI which is situated in the northernmost part of the Lower Citadel of Tiryns. The inscription is interpreted as the first example of an Ugaritic text found outside of the Levant. The text is written from left to right combining Akkadian logographic numerical signs and at least one letter of the regular Ugaritic alphabet. After discussing different possibilities concerning the object’s function, an interpretation as a ›tally stick‹ is proposed, i.e. a mnemonic device to document numbers, quantities or possibly a message, that was used by Levantine or Cypriote specialists for skilled crafting who were working in Building XI on behalf of the palace. The find assemblage in Building XI serves as a reminder that it would be highly misleading to regard oriental objects like the ivory rod with cuneiform signs or wall brackets appearing in a Mycenaean harbor town such as Tiryns as mere ›exotica‹. Instead, contextual analysis demonstrates that the users were well aware of the special significance attached to such objects in the east and employed them in accordance with practices of Near Eastern or Cypriote origin, thus signaling their cultural affiliations.